(untitled) (KYAMC Journal, 2019)
Background: Antimicrobial resistance in health care-associated pathogens is a growing concern for healthcare and for public health. In response to these concerns, medical experts, professional societies and agencies, such as the Centers for Disease Control and Prevention (CDCP), have proposed initiatives to curtail the spread of antimicrobial resistance in pathogenic bacteria. Objectives: The purpose of the study was to observe the disease pattern and demographic characteristics of patient attending at the outpatient department of Otolaryngology in a tertiary care hospital suffering from sore throat and methicillin resistant Staphylococcus Aureus (MRSA) positive pharyngo-tonsillitis. Materials and Methods: This is a retrospective study carried out at the outpatient department of Otolaryngology in Khwaja Yunus Ali Medical College and Hospital for the period of January, 2016 to December, 2017. Data were collected based on history, clinical examinations and culture and sensitivity report of throat swab of the patients. Result: A total of 339 patients were studied of which 49.56% were male and 50.44% were female. The mean age was 30 years; maximum patient (36.28%) belongs to 21-30 years of age. Maximum patient (76%) were come from out of Sirajganj district specially North Bengal. Regarding result of throat swab of C/S 58.11% patients were MRSA positive, 26.84% patients were MRSA negative and15.04% patients has no growth. Conclusion: It is illogical to treat all sore throats with antibiotics. A large scale multi-center study should be performed in the country. A uniform data system should be constructed for Chronic Pharyngo-tonsillitis caused by Methicillin resistant Staphylococcus aureus in Bangladesh. KYAMC Journal Vol. 9, No.-4, January 2019, Page 177-181